Impact of magnetic field and entropy generation of Casson fluid on double diffusive natural convection in staggered cavity. (October 2021) - Hussain, Shafqat; Shoeibi, Shahin; Armaghani, Taher
Abstract: In recent decades, double diffusive natural convention is one of the most widely used subject of study in the field of heat transfer. In this present study, the impact of magnetic field and entropy generation of Casson fluid on double diffisuive natural convention in staggered cavity have been investigated numerically with Galerkin finite element method. The stepped shape cavity is under the uniform inclined magnetic field. In order to strengthen the analysis performed in this study, the designed solver is validated quantitatively against both numerical and experimental data. Various key parameters including entropy generation, Hartmann number, Rayleigh number, Casson parameter (β), Lewis number, are studied in the stepped shape enclosure. The results showed that the Kinetic energy in β = 10 was improved 7.44 times more that that of in β = 0.1 in the same Ha = 0. Also, the Lewis number has an inverse and direct effects with Nusselt and Sherwood number, respectively. Moreover, the highest mean Nusselt number was obtained in Le = 0.1 and Ra = 10 7 and is equal to 19.3.